Analisis Kecelakaan Lalu Lintas (Ruas Jalan Km 10 - Km 17 Gambut) - Robiatul Adawiyah; Rahmatullah Rahmatullah; Adhi Surya (Jurnal Teknologi Berkelanjutan, 2021)
With all the developments that have occurred, of course there are several transportation problems, one of which is a traffic accident. Starting from minor accidents, serious accidents that caused a lot of material loss and casualties. The purpose of this study was to determine the number of traffic accidents and areas prone to traffic accidents on the Km 10 - Km 17 Peat Road. In analyzing traffic accidents at the research location, data that supports the research is needed, namely secondary data obtained from the Banjar Police. Research Results The number of traffic accidents in 2019 that occurred on the Km 10 - Km 17 Peat Road was 31 times with 0% serious injuries, 74% minor injuries, 26% died. Accident-prone areas on the Road Km 10 - Km 17 Peat are in segment 1 (km 10 - km 11), segment 2 (km 11 - km 12), segment 3 (km 12 - km 13), segment 5 (km 14 - km 15). It is hoped that all road users will remain careful and for the Government concerned that there is maintenance and maintenance on every road segment that is not getting enough maintenance because the road environment also affects traffic accidents.